Nilai-Nilai Moral dalam Novel Assalamualaikum Calon Abi Karya Arthar Puspita Maghfiroh - Khasanah, Afita Dwi; Israhayu, Eko Sri (Ruang Kata, 2024)
This study aims to describe the moral values contained in the novel Assalamualaikum Calon Abi by Arthar Puspita Maghfiroh. This research uses descriptive qualitative method with moral value approach. The data source used is the novel Assalamualaikum Calon Abi by Arthar Puspita Maghfiroh with 376 pages and the data in this research is in the form of dialog, paragraphs or sentences that contain moral values. Data collection is done by reading and recording techniques and analyzed by identifying the form of moral values, classifying, and inferring or drawing conclusions from the data obtained. Based on the results of the study, there are moral values in the novel Assalamualaikum Calon Abi by Arthar Puspita Maghfiroh consisting of moral values of human relationships with themselves, moral values of human relationships with other humans, and moral values of human relationships with God.